Gandhi - Attenborough, Richard (Columbia Pictures, 2001)
Traces the life of Mohandas K. Gandhi, stressing his philosophy of nonviolence as a technique for politic change from his activities in South Africa in the Indian Congress Party (1893) through his return to India (1915), his role in the Indian National Congress Party, and his various campaigns and struggles for Indian independence ends with his death by assassination in 1948, just a few months after Indian independence.